The autobiography and songs of Dri-med-gliṅ-pa = Bdag ʼdra Theg gliṅ ʼGro don mthar phyin nam O rgyan Dri med gliṅ pa gar dbaṅ bdud ʼdul las rab rtsal du ʼbod paʼi rnam thar mgur ʼbum don gyi me loṅ tshaṅs paʼi sgra dbyaṅs - Dri-med-gliṅ-pa, Gter-ston, 18th cent (Kunsang Topgay, 1978)
Writings of a Nyingmapa visionary of central Tibet.